Improving Resilience in Water Distribution Systems: An Application of the House of Risk Method at PDAM Gowa Unit Tompobulu - Malik, Rahmaniah; Safutra, Nur Ihwan; Fole, Asrul; Pangestu, Fausan Amal (Jurnal Sistem Teknik Industri, 2024)
PDAM Gowa, a local government-owned company, plays a vital role in supplying clean water to the Tompobulu community in Gowa District. However, ensuring efficient and reliable water distribution poses challenges at the local and regional levels. This research focuses on enhancing the resilience of the water distribution system to mitigate various risks. The study utilizes the House of Risk (HOR) method for effective risk management and developing suitable mitigation strategies within PDAM's framework. The research identifies 10 risk events and 17 risk factors that affect water distribution in PDAM. Key risks include pipe leakage and supply disruptions. To mitigate these risks, the study proposes nine actionable recommendations for PDAM Gowa Unit Tompobulu. These recommendations involve regular maintenance of distribution infrastructure and equipment to ensure system quality and reliability. Additionally, improving pipe network condition monitoring, implementing leakage control policies, and fostering collaboration with stakeholders to address water supply disruptions are crucial mitigation measures. This research significantly contributes to understanding the risk management associated with water distribution in PDAM. By implementing the recommended mitigation strategies, PDAM Gowa Unit Tompobulu can reduce water distribution risks, enhance system efficiency, and provide improved clean water services to consumers. Moreover, the study has the potential to drive scientific progress and promote the development of best practices and technologies in the drinking water industry.